PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP HASIL BELAJAR IPS SISWA KELAS V SDN 034 TARAI BANGUN - Fatkul Jannah; Eddy Noviana; Hamizi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract:Social learning procesed at grades fifth was les actives because teacher often to explained study material that made student’s less do question-answers and issues its opinion in learning,it is coused of reducing student just read social study material.The problem in this research is to be know influence off implement model cooperative learning type CIRC to student’s social learning of grades fifth at SDN 034 Tarai Bangun. The purpose of this research is to be know influence of implement model cooperative learning type CIRC to student’s learning result social students of grades fifth at SDN 034 Tarai bangun of school years 2013/2014. This research is observational that gets to form experiment with two sample group which is that consisting of experiment clas and control class. Analyze pretest data and postteston experiment class and control class is happening increase learning result. Experiment class on average pretest in 50,7 worked up 74,1 on posstest with increasing N-Gain is 0,49 (medium). On class controls average pretest is 52,42 worked up as 68,18 on posttest with increasing N-Gain is 0,32 (medium). Result t-test on α = 0,05 by dk=77 acquired ttable = 2,000. Base analyzed data is gotten tcomputing = 2,45, so, tcomputing= 2,45>ttable=2,000, it means there is result study diffrence among experiment class and control class. Form analyze data can be seen that learned rsult experiment class overbid than control class. Result observationaling to point out that avalable big affecting of model cooperative learning type CIRC is 26% to usufruct social studyings student class experiment.Keyword : CIRC, Learning Result.